2020
DOI: 10.1029/2020jd033162
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Resolved Mixing States and Sources of Amine‐Containing Particles in the East China Sea

Abstract: Single-particle aerosol mass spectrometry was employed during a cruise campaign from 3 to 27 June 2017 to investigate the mixing states and sources of amine-containing particles in the East China Sea. A total of 271,160 particles were successfully identified, and 19,861 of these particles contained amines. Monomethylamine (MMA), trimethylamine (TMA), and diethylamine (DEA) were the most abundant amines. They accounted for 50%, 16%, and 29%, respectively, of the amine-containing particles. The size distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…In particular, the influence of coal combustion associated with heating and industrial production is an important feature that distinguishes the difference of amine sources between the YRD and PRD areas and the northern areas. It should be pointed out that the above analysis identified the origins of potential contributors (i.e., gas‐phase amines) to the formation of particle‐phase amine salts, as suggested by many previous studies (Berta et al., 2023; Cheng et al., 2018; Liu et al., 2020; Zhong et al., 2021; Zhou et al., 2019). Recently, a study about the contributions of anthropogenic sources to amines in PM 2.5 suggested that the formation of particle‐phase amine salts (e.g., MA and DMA) was closely associated with the origins of gas‐phase amines (C. Liu et al., 2022).…”
Section: Resultssupporting
confidence: 60%
“…In particular, the influence of coal combustion associated with heating and industrial production is an important feature that distinguishes the difference of amine sources between the YRD and PRD areas and the northern areas. It should be pointed out that the above analysis identified the origins of potential contributors (i.e., gas‐phase amines) to the formation of particle‐phase amine salts, as suggested by many previous studies (Berta et al., 2023; Cheng et al., 2018; Liu et al., 2020; Zhong et al., 2021; Zhou et al., 2019). Recently, a study about the contributions of anthropogenic sources to amines in PM 2.5 suggested that the formation of particle‐phase amine salts (e.g., MA and DMA) was closely associated with the origins of gas‐phase amines (C. Liu et al., 2022).…”
Section: Resultssupporting
confidence: 60%
“…The number fraction of particles containing a specific ion in total particles was obtained through a conventional ion search procedure with COCO v1.4 software. The particle size detected by SPAMS was not scaled by a scanning mobility particle sizer for potential deviations caused by size-dependent particle transmission of the aerodynamic lens employed in SPAMS; nevertheless, it still captured the underlying trend of particle size evolution. ,, …”
Section: Methodsmentioning
confidence: 99%
“…The particle size detected by SPAMS was not scaled by a scanning mobility particle sizer for potential deviations caused by size-dependent particle transmission of the aerodynamic lens employed in SPAMS; 30−32 nevertheless, it still captured the underlying trend of particle size evolution. 29,33,34 WRF-CMAQ Model Simulation and Quantification of Meteorological Contribution. The weather research and forecasting (WRF v3.7) and community multiscale air quality (CMAQ v5.0.2) models were employed to simulate the air quality during the SFs of 2022 and 2023, under the corresponding meteorological conditions without considering fireworks (termed the base case).…”
Section: Spams Datamentioning
confidence: 99%
“…The atmosphere consists of 30%–80% of marine fine particle matters (Q. Fu et al., 2008; H. W. Xiao et al., 2017), and secondary inorganic ions have a great effect on hydroscopic properties and particle acidity. This may influence Earth's radiation balance, fog formation and cloud physics, and visibility degradation, as well as human health (Z. Liu et al., 2020; Zou et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This may influence Earth's radiation balance, fog formation and cloud physics, and visibility degradation, as well as human health (Z. Liu et al, 2020;Zou et al, 2017).…”
mentioning
confidence: 99%